2009
DOI: 10.1002/j.0022-0337.2009.73.12.tb04833.x
|View full text |Cite
|
Sign up to set email alerts
|

Educational Experiences and Preparedness in Dental Anesthesia: Five‐Year Outcome Assessment and Conclusions

Abstract: A mail survey of 2003-07 dental school graduates was undertaken by the Department of Anesthesiology at the University of Pittsburgh School of Dental Medicine to assess the strengths and weaknesses of the predoctoral curriculum in anesthesia and to determine the preparedness of practicing dentists to provide anesthesia services for their dental patients. Subsets of the survey responses were created to specifically evaluate the effectiveness of an advanced selective program in sedation offered to approximately t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“… 22 Finally, this highlights the importance of establishing high-quality dental education programs to prepare undergraduate dental students for and to increase their willingness to treat patients with special needs now and throughout their careers. 23 , 24 Obviously, there are many issues that influence dental care providers’ willingness and competence to treat patients with special needs. 25 It may be valuable to better understand dental education programs with regard to the treatment of patients with special needs and the impact it has on dental care practitioners’ willingness to treat this population.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 Finally, this highlights the importance of establishing high-quality dental education programs to prepare undergraduate dental students for and to increase their willingness to treat patients with special needs now and throughout their careers. 23 , 24 Obviously, there are many issues that influence dental care providers’ willingness and competence to treat patients with special needs. 25 It may be valuable to better understand dental education programs with regard to the treatment of patients with special needs and the impact it has on dental care practitioners’ willingness to treat this population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have been directed toward dental students and dental health care providers to measure the factors influencing their behaviors that may limit or improve the access of patients with special needs to dental clinics ( Table 1 ). 1 , 3 , 7 , 13 , 16 , 19 , 22 24 , 26 30 These studies attempted to measure the preparedness, 9 , 13 , 26 , 27 experience, 19 , 22 , 23 , 26 , 27 knowledge, 3 attitudes, 13 , 26 , 29 and perceptions 7 , 24 , 31 of the dental care providers in regard to treating patients with special needs. The studies were directed at different target populations, where some targeted decision makers at dental teaching institutions, 1 , 3 , 27 while others targeted clinical dental care providers 29 – 32 and some studies targeted alumni and/or current students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research with dental school graduates concerning their desire for education about sedation seems to contradict this response in our study. In Moore et al's survey of dental school graduates from 2003 to 2007, 44% of general dentists reported that a lack of training/experience or knowledge was a major reason for not offering sedation in their general dental practices, and the respondents’ written comments indicated a desire for a greater number of clinical experiences involving sedation procedures in the predoctoral curriculum 24 . In 2006, Boynes et al assessed the quality and quantity of sedation education in U.S. dental schools among general dental practitioners who had graduated in 2003 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In summary, Spain shares a series of international factors that seriously affect the oral health of its population and require consensus‐based training in CS to enable recent graduates to use this technique safely, a task not exempt from difficulties according to the universities of different European and non‐European countries who share our concerns, including the United Kingdom and Ireland (Leitch & Jauhar, ), the United States (Boynes, Lemak, & Close, ), Australia (Moore, Boynes, Cuddy, Giovannitti, & Zovko, ), Japan (Morse, Sano, Fujii, & Kanri, ), and Jordan (Al‐Shayyab, Ryalat, Dar‐odeh, & Alsoleihat, ).…”
Section: Introductionmentioning
confidence: 99%